Review study in efficacy of silver nanoparticles in preventing and treating pediatric dental caries - Dr.Roaa Mohammad AlDomyati; Dr.Waleed Abdulrahim Aljehani; Dr.Hussam sultan Farrash; Dr.Anmar Essam Kattan; Dr.Rozan Sameer A Nasruddin; Dr.Omar Mohammed abo nawas; Dr.Wail Hisham Ragkhan; Dr. Abdullah Sameer Kaki; Dr. Maha Suliman Tayeb; Dr. Salwa Abdulmonem Mohammed Alsaid; Dr.Moayad Adnan Diwan; Dr.Rasha Abdulkarim Alshehri; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Nanoscience and nanotechnology are nascent disciplines focused on the synthesis and utilization of nanoscale materials and structures. Metallic nanoparticles and metallic oxides are widely utilized in dentistry due to their ability to disrupt bacterial metabolism and inhibit biofilm development. Silver nanoparticles (AgNPs) represent a category of zero-dimensional materials characterized by unique morphologies. The metallic nanoparticles have considerable antibacterial action through ion release, oxidative stress induction, and non-oxidative processes. Metallic silver has been recognized for its antibacterial properties since antiquity. Over the years, silver-containing compounds have been utilized in many forms to address multiple medical ailments. The integration of silver nanoparticles into dental materials may improve their mechanical qualities and antibacterial efficacy. Consequently, a growing array of dental materials including silver nanoparticles is being created to enhance patients' overall oral health. This review paper is to examine the literature about the unique properties of silver nanoparticles and their applications in pediatric dentistry, as well as their effectiveness in the prevention and treatment of dental caries.